2014
DOI: 10.1016/j.scr.2014.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Ptp4a3 reduces clonogenicity and tumor-initiation ability of colitis-associated cancer cells in mice

Abstract: The PTP4A3 gene is highly expressed in human colon cancer and often associates with enhanced metastatic potential. Genetic disruption of the mouse Ptp4a3 gene reduces the frequency of colon tumor formation in mice treated in a colitis-associated cancer model. In the current study, we have examined the role of Ptp4a3 in the tumor-initiating cell population of mouse colon tumors using an in vitro culture system. Tumors generated in vivo following AOM/DSS treatment were isolated, dissociated, and expanded on a fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 21 publications
4
23
0
Order By: Relevance
“…Depletion of PTP4A3 reduced TNBC tumor growth in vivo by reducing proliferation marker (Ki67), phospho-ERK1/2 and p38 levels, while increasing apoptotic markers (1). Highly elevated PTP4A3 expression is also associated with enhanced tumor formation and metastasis by reducing tumor initiating cells in colon cancer mouse models (46). Collectively, these studies demonstrate that oncogenic PTPs play a critical role in tumor initiation, progression and metastasis by enhancing signaling pathways and serving as valuable targets for cancer therapy.…”
Section: Phosphatases As Oncogenesmentioning
confidence: 99%
“…Depletion of PTP4A3 reduced TNBC tumor growth in vivo by reducing proliferation marker (Ki67), phospho-ERK1/2 and p38 levels, while increasing apoptotic markers (1). Highly elevated PTP4A3 expression is also associated with enhanced tumor formation and metastasis by reducing tumor initiating cells in colon cancer mouse models (46). Collectively, these studies demonstrate that oncogenic PTPs play a critical role in tumor initiation, progression and metastasis by enhancing signaling pathways and serving as valuable targets for cancer therapy.…”
Section: Phosphatases As Oncogenesmentioning
confidence: 99%
“…Mouse CRC cells were derived from our previously described primary colon tumor epithelial cells, which were obtained from Ptp4a3 fl/fl mice treated with azoxymethane and dextran sodium sulfate (34). Mouse CRC cells were initially plated on a confluent feeder layer of lethally irradiated (80 Gy) LA7 rat mammary tumor cells (CRL-2283; American Type Culture Collection, Manassas, VA, USA) at ;80,000 cells/cm 2 and in DMEM/F12 medium with 0.5% fetal bovine serum (FBS), 25 mg/ml gentamycin (MilliporeSigma, St. Louis, MO, USA), and 1% insulin-transferrin/selenium (Mediatech, Manassas, VA, USA).…”
Section: Cells and Reagentsmentioning
confidence: 99%
“…Mouse CRC cells were initially plated on a confluent feeder layer of lethally irradiated (80 Gy) LA7 rat mammary tumor cells (CRL-2283; American Type Culture Collection, Manassas, VA, USA) at ;80,000 cells/cm 2 and in DMEM/F12 medium with 0.5% fetal bovine serum (FBS), 25 mg/ml gentamycin (MilliporeSigma, St. Louis, MO, USA), and 1% insulin-transferrin/selenium (Mediatech, Manassas, VA, USA). When cells reached ;70% confluence, Ptp4a3 fl/fl cells were detached from the feeder layer by incubation with Earle's balanced salt solution/1 mM EGTA/1% HEPES followed by 0.25% trypsin/0.1% EDTA as previously described (34). A mouse CRC feeder layer-independent cell population was generated by serially decreasing the feeder layer at the time of passaging (approximately once per week with a 20% reduction in number of cells in feeder layer) and increasing the FBS concentration (15% increase in concentration at time of passage).…”
Section: Cells and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…PRL-2 has been reported to increase EPO and IL3 response in hematopoietic cells (32) and play critical roles in regulating HSC self-renewal (33). A previous study reported that genetic disruption of PRL-3 reduces clonogenicity and growth of CD133 þ mouse colon cancer cells in an in vitro culture system (34). CD133 is also a specific marker for human hematopoietic stem/progenitor cells (35,36).…”
Section: Discussionmentioning
confidence: 99%